Evaluation Of Recurrent Abdominal Pain In Children Attending Outpatient Clinics In Erbil - Hamad, Snur Hamad Ameen; Al-Talabany, Shayda Ziyad Jamil (Adolescência e Saúde, 2026)
Background: Recurrent abdominal pain (RAP) is a common yet frustrating issue for children, often resulting in numerous doctor visits. The key to successful treatment lies in accurately distinguishing between physical (organic) and non-physical (functional) triggers. This study was designed to explore the various causes of RAP, evaluate its clinical symptoms, and understand how it affects the menta and social well-being of both the children and their families. Patients and methods: We conducted a case series study involving 100 children (ages 3-15) who sought help for RAP at outpatient clinics in Erbil between August 2024 and August 2025. To better understand the nature of their pain, we analyzed their clinical symptoms, psychological stressors, and diagnostic test results. Results: The majority of the participants were boys (62% and fell within the 6-11 age range (64%). Pain was typically felt around the belly button (40%) or spread throughout the abdomen (39%), with 68% of children experiencing these episodes daily or several times a week. Stress and anxiety were major triggers.While organic causes-such as H. pylori, urinary tract infections, and giardiasis-were found in 32% of cases, functional issues were much more prevalent. Interestingly, frequent pain was strongly linked to lower weight, shorter stature, and lower socioeconomic status. While medication was the most frequent treatment, it was usually part of a broader management plan. Ultimately, the study confirmed that RAP significantly disrupts family life and that functional causes are the leading driver of child abdominal pain in Erbil. Conclusion: Managing RAP requires a "big picture" approach that looks beyond just physical symptoms to include diet, lifestyle, and mental health. By identifying these issues early and using a team-based medical approach, we can better protect a child's long-term health and development.